Intra-Industry Trade in Tourism Services - Nuno Carlos LEITÃO (Theoretical and Applied Economics, 2011)

(untitled)
Usually the tourism flows are explained by demand, economic growth, and revealed comparative advantage (neoclassic trade theory). This manuscript examines the link between intra-industry trade and international tourism flows. We have examined the Portuguese intra-industry trade in this sector. The analysis apply the static (Grubel and Lloyd) and dynamic index (Brülhart). Our results show that the tourism services are important for a small economy such as Portugal. The intra-industry trade is very significant between Portugal and the following countries: Spain, USA, Italy, Greece, Turkey and Canada.